Aortic angiosarcoma leading to paraplegia: a case report - Li, Jing; Sun, Jiubo (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAortic angiosarcoma is a rare disease with atypical clinical symptoms. It often initially presents with embolic phenomena, such as lower limb arterial embolism, visceral embolism, or cerebral embolism, or as renovascular hypertension.MethodsThere are no reported cases in the literature of spinal cord embolism caused by this condition. We report a case of a 76-year-old female patient whose abdominal CT showed a soft tissue mass in the left hip, involving the sacrum and iliac bone.ResultsAortic CTA revealed irregular filling defects in the aortic arch and descending aorta, highly suggestive of a tumor. A biopsy of the left hip mass confirmed the diagnosis of angiosarcoma. Immunohistochemistry results were positive for Vimentin, CD31, and ERG. Based on the patient's CTA findings, a diagnosis of aortic angiosarcoma with left hip soft tissue metastasis was made. The patient developed paraplegia and lower limb arterial embolism and died shortly afterward. This article briefly reviews the literature on aortic angiosarcoma.ConclusionsThe purpose of this case report is to highlight the importance of monitoring common embolic sites in clinical practice, while also considering the possibility of rare sites, such as spinal cord embolism.